Methods of Skull Base Repair Following Endoscopic Endonasal Tumor Resection: A Review - Hannan, Cathal John; Kelleher, Eoin; Javadpour, Mohsen (Frontiers in Oncology, 2020)
Following the introduction of fully endoscopic techniques for the resection of pituitary tumors, there was a rapid expansion of the indications for endonasal endoscopic surgery to include extrasellar tumors of the skull base. These techniques offer significant advantages over traditional open surgical approaches to the skull base, including improved tumor resection and better post-operative neurological outcomes. Following their introduction however, the initial rate of post-operative CSF leak was unacceptably high. Post-operative CSF leak following skull base surgery is a major source of morbidity, and can lead to the development of life-threatening intracranial infection. The use of vascularized naso-septal flaps transformed the management of these patients, significantly reducing the rate of post-operative CSF leak and increasing the number of patients that could benefit from this less invasive treatment modality. Adequate repair of iatrogenic defects in the skull base is of crucial importance for patients with skull base tumors, as the development of a post-operative CSF leak and the associated complications can significantly delay the administration of the adjunctive oncological therapies these patients require. In this review, we provide an overview of the latest evidence regarding skull base reconstruction following endoscopic skull base surgery, and describe the skull base repair technique in use at our institution.